2018
DOI: 10.1097/mlr.0000000000000910
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Processes and Patient Experiences in the Patient-centered Medical Home

Abstract: Although some organizational processes relate to patients' experiences with care irrespective of the background of the patient, further efforts are needed to align practice efforts with patient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Prior work supports the need for the patient voice and feedback on organizational processes in our primary care redesign efforts. (8,9] Moreover, we found that patient experience with their primary care provider did appear to influence no show rates. Practices should make efforts to minimize appointment no shows, which have shown to result in significant financial costs for practices and decreased value of care for patients.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Prior work supports the need for the patient voice and feedback on organizational processes in our primary care redesign efforts. (8,9] Moreover, we found that patient experience with their primary care provider did appear to influence no show rates. Practices should make efforts to minimize appointment no shows, which have shown to result in significant financial costs for practices and decreased value of care for patients.…”
Section: Discussionmentioning
confidence: 79%
“…Goldman et al evaluated this and found that a patient’s visit experience, if negative, strongly predicted future no shows ( 25 ). There is also prior evidence that patient overall experience with visit is dictated by their experience with their primary care provider ( 8 , 9 ). Future work should consider developing and implementing initiatives that improve provider–patient relationships and communications and evaluate the effects on appointment no shows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data review is one of the critical factors that leads to practice success in health system redesign and contributes to cost savings. 4,[10][11][12] Larger practices are more likely to have personnel dedicated to data generation and interpretation, whereas smaller practices are most likely to lack resources to review, interpret, and act on data that are mailed or placed on web servers for use. 13 For effective engagement and action by practices, use of practice transformation tools to engage practices in quick reviews of actionable data is critical.…”
Section: Discussionmentioning
confidence: 99%